Deformation Behavior of 2D Composite Cellular Lattices of Ceramic Building Blocks and Epoxy Resin - Eichhorn, Franziska; Keppner, Felix; Köllner, David; Fey, Tobias (Advanced Engineering Materials, 2021)
2D lattice structures with ordered cell designs based on honeycombs are built from modular composites of ceramic building blocks and epoxy resin. The variation of structural parameters as slenderness t2 g−1 and piezoelectric active area q changes the cell design. finite element method (FEM) simulations based on algorithm-generated models within a structural parameter range determine the effect of thermal expansion of different materials (αMaterial) on the mechanical behavior in plane strain mode representative of piezoelectric excitation. The stress distribution σyy and strain amplification ay as a function of deformation are analyzed for Al2O3−PZT and PZT−PZT building block composites. The aim herein is to increase ay by modifying structure design. Furthermore, zero deformation with simultaneously occurring stresses is investigated.
CRIS-Team Scopus Importer:2021-08-27
Keywords: cellular solids; mechanical deformation behaviors; strain amplification; thermal deformation behaviors

Improved Mechanical Amplification of Monolithic PZT and PZT Composite via Optimized Honeycomb Macrostructures - Eichhorn, Franziska; Bytomski, Julia; Gerauer, Markus; Kakimoto, Ken Ichi; Fey, Tobias (Materials, 2022)
Honeycomb-based, modular composites with a relative density of 0.3948 and a slenderness ratio Lges/t of 6.48 were fabricated on PZT building blocks connected with a PZT-filled phenyl silicone resin. The macro- and micro-structure, phase composition, and the interface between the two materials were analyzed by SEM and image analysis techniques. The mechanical in-plane strain response was determined with uniaxial compression tests and the transversal piezoelectric strain response was determined by applying an electric field. These deformations were analyzed by a 2D digital image correlation analysis to calculate the mechanical strain amplification of monolithic and composite PZT lattice structures. Compared to bulk PZT, the piezoelectric strain amplification in the Y-direction |aypiezo| was higher by a factor of 69 for the composite and by a factor of 12 for the monolithic cellular PZT lattice, when it was assumed that the ratio of the deformation of the bulk material to bulk material was 1. The mechanical amplification of the composite lattices increased up to 73 and that of the cellular PZT lattices decreased to 12. Special focus was given to the fracture behavior and the interface of the PZT/PZT-filled phenyl silicone resin interface.
CRIS-Team Scopus Importer:2022-12-09
Keywords: cellular solid; ceramic composites; ceramics-functional; ceramics-structural; functionalization; piezoceramic composites; piezoelectric materials; strain amplification

Influence of Cell Size on Mechanical and Piezoelectric Properties of PZT and LNKN Ceramic Foams - Eichhorn, Franziska; Biggemann, Jonas; Kellermann, Simone; Kawai, Akinobu; Kato, Kensuke; Kakimoto, Ken-Ichi; Fey, Tobias (Advanced Engineering Materials, 2017)
Piezoceramic foams made of lead zirconate titanate (PZT) and lithium sodium potassium niobate (LNKN-6) containing an open porosity >75 vol% are manufactured with varying cell size from 1369 to 265 μm and accordingly, strut size from 346 to 46 μm by replica method. Pore size distribution and strut thickness are determined by X-ray micro tomography investigations of PZT foams with 10, 30, 45, and 80 pores per inch (ppi). Fracture strengths σb between 0.29 and 1.52 MPa (PZT) and 0.04 and 0.07 MPa (LNKN-6) are determined by compression test and compared to Gibson and Ashby's model of open- and closed-cell foams and in dependence of the cell size. The longitudinal and transversal coupling coefficients d33 and d31 decrease in a range of 38 to 178 pCN−1 or −13 to −100 pCN−1 compare to dense reference material. In dependence of the cell size, the values of the coupling coefficients change about 79–93%. The relative permittivity decreases 93% by decreasing the cell size of the PZT and LNKN-6 foams.
Keywords: lead-free; piezo ceramic foams; pore network; porous structures

Influence of Porosity Orientation on Physical Properties in Porous PZT Ceramics - Eichhorn, Franziska; Kakimoto, Ken ichi; Greil, Peter; Fey, Tobias (Advanced Engineering Materials, 2019)
Orientation of porosity in porous media influences the pore network and their physical properties. Sacrificial cellulose templates arranged in different stacked layer orientation configurations with various distortion form the oriented pore network. The templates are embedded into non-aqueous lead zirconate titanate (PZT) slurry (solid fracture of 48 vol%) and burn-out while sintering. The porous PZT ceramics have a mean porosity of up to 39% Microcomputer tomography (μCT) measurement and SEM analysis are used for pore network analysis. The longitudinal and transversal piezoelectric coefficients (d33 and d31) and the relative permittivity ϵr vary between 15 and 98% according to the reference sample. The bending strength σb (double ring test) is reduced by 60% with increasing porosity compared to the dense sample.
CRIS-Team Scopus Importer:2019-06-18
Keywords: hydrophone; piezoelectric; pore network; pore orientation; porous ceramic

Paper-Derived Ferroelectric Ceramics: A Feasibility Study - Menge, Georg; Lorenz, Hannes; Fu, Zongwen; Eichhorn, Franziska; Schader, Florian; Webber, Kyle Grant; Fey, Tobias; Greil, Peter; Travitzky, Nahum (Advanced Engineering Materials, 2018)
Keywords: Microstructure; Multilayer BaTiO3; Piezoelectric properties; Preceramic paper

Phase evolution, filler-matrix interactions, and piezoelectric properties in lead zirconate titanate (PZT)-filled polymer-derived ceramics (PDCs) - Eichhorn, Franziska; Kellermann, Simone; Betke, Ulf; Fey, Tobias (Materials, 2020)
PZT-silsesquioxane-based 0-3 hybrid materials are prepared by mixing lead zirconate titanate (Pb(Zr, Ti)O3; PZT) powder with a [R-SiO3/2]n (R = H, CH3, CH=CH2, C6H5) silsequioxane preceramic polymer. APZT load up to 55 vol. % can be reached in the final composite. The piezoelectric and mechanical properties are investigated as a function of the filler content and are compared with theoretical models and reference samples made of the pure preceramic polymer or PZT filler. The piezoelectric response of the composites, as expressed by the relative permittivity and the piezoelectric coefficients d33 and g33, increases with an increasing PZT content. The bending strength of the composites ranges between 15 MPa and 31 MPa without a clear correlation to the filler content. The thermal conductivity increases significantly from 0.14 W m-1 k-1 for the pure polymer-derived ceramic (PDC) matrix to 0.30 W m-1 k-1 for a sample containing 55 vol. % PZT filler. From X-ray diffraction experiments (XRD), specific interactions between the filler and matrix are observed; the crystallization of the PDC matrix in the presence of the PZT filler is inhibited; conversely, the PDC matrix results in a pronounced decomposition of the filler compared to the pure PZT material.
CRIS-Team Scopus Importer:2020-04-17
Keywords: Composite material; Filler matrix interaction; Lead zirconate titanate (PZT); Piezoelectric material; Polymer-derived ceramic (PDC)

Porous piezoelectric ceramics with 3-3-connectivity fabricated by impregnation of cellulose paper structures - Eichhorn, Franziska; Stenzel, Alexander; Weisenseel, Bastian; Travitzky, Nahum; Kakimoto, Ken-Ichi; Greil, Peter; Fey, Tobias (Materials Letters, 2017)
Keywords: Paper derived ceramic; Piezoelectric properties; Cellulose fiber paper; Hydrophones; Porous piezoceramic

Secondary Pyroelectric Effect and Figure of Merit of Ferroelectric 0–3 Composites - Ando, Daisuke; Eichhorn, Franziska; Fey, Tobias; Kakimoto, Ken ichi (Advanced Engineering Materials, 2019)
By mixing lead-free piezoelectric Li0.06(Na0.50K0.50)0.94NbO3 (LNKN) ceramic particles and polysiloxane, the authors synthesize a novel pyroelectric element that exhibits an enhanced secondary pyroelectric effect. The composite with an LNKN filler ratio of 30 vol% exhibits a homogeneous microstructure and a strong contact between the LNKN filler and the polysiloxane matrix. Thus, the secondary pyroelectric effect originating from such an interaction accounts for approximately half of the total pyroelectric coefficient (i.e 29 μC/m2K) and enhanced the figure of merit of the composite (1.1 μC/m2K).
CRIS-Team Scopus Importer:2019-06-18
Keywords: composite; lead-free piezoelectric material; pyroelectric; secondary pyroelectric effect; thermal expansion

Stress and Deformation Behavior of 2D Composite Cellular Actuator Structures of Ceramic Building Blocks and Epoxy Resins - Eichhorn, Franziska; Schiegerl, Helmut; Köllner, David; Kakimoto, Ken-Ichi; Fey, Tobias (physica status solidi (b), 2022)
2D actuator composite structures are fabricated of lead zirconate titanate (PZT) and Al2O3 building blocks with an epoxy resin matrix. This novel modular concept gives the possibility to create complex geometric structures where the structure itself tailors the physical properties. To improve the possibilities of excitation or loading and determine the influence of the geometric parameters as slenderness ratio t2 · g−1 and active area Aactive finite element (FE) simulations are used. The stress distribution σyy within the unit cell and the resulting strain amplification ay are tested with different mechanically coupled thermal excitation modes. A homogeneous excitation of the PZT building blocks and a maximum Aactive of 24% led to a maximum of strain amplification and a reduction of induced tensile stresses. In addition, zero deformation could be generated by modifying the structure design with a slenderness ratio of 0.5. Further geometric variations offer the potential to increase the strain amplification.
CRIS-Team Scopus Importer:2022-04-15
Keywords: cellular ceramics; deformation behaviors; finite-element analyses; strain amplifications